Estudo da participação de metais traço em uma linha d`água de um tanque de cultivo de camarão marinho do município de Santa Rita-PB - Barros, Sara Regina Ribeiro Carneiro de (2006)
Brazil, it is nowadays, is one of the main producing of sea shrimp of the world. Due to this position, necessary that is done there are discussions that relates this activity to the environmental preservation, aiming avoid, among others problems, irreparable damages to the mangroves ecosystem and modification in the water quality of the rivers that receive effluent of the ponds.In this sense the metals behavior comprehension in natural waters is indispensable. Some metals besides being essential nutritious, also are toxic to the aquatic organisms. And, they constitute in an agent polluter, in potential. In this context, in this work, were collected waters of a tank of species marine shimp cultivation Litopenaus vanamei, located in the district of Santa Rita, estuary area of the Ribeira river, in Paraiba state. Due to the contribution of the metals Cu, Fe and Zn in the column of water of the creation tanks, it tried to evaluate the contribution of each one of the metallic species. Like this, for seven months, samples of water of the shrimp pound were collected and separate in the fractions: (A) soluble fraction (filtered through membrane 0,45 μm); (B) labile fraction (extraction to cold of the particulate matter); (C) total fraction (extrated by acid under heating of the particulate matter). In addition to the quantity of metals, they were determined the variations of OD (Dissolved Oxygen), SPM Suspended Particulate Matter, Salinity, pH and Temperature. By observing the obtained data, about the pH influence and OD on the metals partitioning one verifies that OD in the partition of the metals, OD is more correlated with the fractions A and B of Fe and Zn, while the pH influences more the fraction C of all the metals. So much SPM, Salinity and the partitioning of the metals enhanced differences among the months, but no so significantly in the heights of water column. Besides, it was also observed correlation among fraction C of Zn and Salinity, and in smaller extension, among fraction C of Fe and this parameter. Before the high complexity and specificity of the waters of shrimp cultivation, owed to the presence of the natural aquatic biotic (phyto and zooplankton), the ration composition (proteins, vitamins, micronutrients, etc.) in addition to the peculiarities of the estuary waters, they turn the creation tanks, extremely dynamic and atypical systems